Setting a specifications for E-learning standard at the Universidad del Quindio (Revista de Investigaciones Universidad del Quindío, 2016)
The increase in the supply of online courses is solution for a given sector of the population breakthroughs barriers of space and time, individual training and learning different rhythms. This growth comes in many institutions of individual initiatives; it is sometimes messy and chaotic, which requires focusing on new problems. One is the lack of uniform standards of academic spaces in the same university or even in the same program. This research was initially proposed a study of online courses at the University of Quindío and in the light of international standards in E-learning, generate a set of specifications that promote the normalization and standardization adapted to regional.
Keywords: Standards; virtual education; E-learning; educational quality online courses